Study on Dynamic Process Characteristics of CHP Unit With Variable Load Based on Working Point Linearization Modeling - Huang, Yuehua; Chen, Qing; Ye, Jing; Lu, Tianlin (Frontiers in Energy Research, 2022)
In view of the difficulty of applying the refine modeling of combined heat and power (CHP) units to the optimization scenario of integrated energy system, a CHP unit model based on working point linearization modeling is proposed and its variable load characteristics are analyzed. Firstly, the dynamic coupling relationship of CHP unit is analyzed, and the nonlinear dynamic model of the unit is constructed. Then, under the pure condensation and heating conditions, the linearized Laplace transform model of working point is established, and the variable load capacity under the independent action of control variables is analyzed to test the availability of Laplace model. On this basis, the dynamic adaptive particle swarm optimization algorithm is used for multivariable cooperative control to test the open-loop characteristics of the variable load capacity of the unit. At the same time, the control strategy of electro-thermal cooperation and safety self-test is designed to adjust the control variables, and test the closed-loop characteristics of the unit's regulation ability. Finally, a 300MW steam extraction CHP unit is taken as an example to verify the applicability of the unit model and the effectiveness of the control strategy.